2021
DOI: 10.1136/bmjopen-2020-044769
|View full text |Cite
|
Sign up to set email alerts
|

Associations of diarised sleep onset time, period and duration with total and central adiposity in a biethnic sample of young children: the Born in Bradford observational cohort study

Abstract: ObjectivesTo investigate associations of parent-reported sleep characteristics with adiposity levels in a biethnic sample of young children.DesignA cross-sectional observational study.SettingThe Born in Bradford 1000 study, UK.ParticipantsChildren aged approximately 18 months (n=209; 40.2% South Asian; 59.8% white) and 36 months (n=162; 40.7% South Asian; 59.3% white).Primary and secondary outcome measuresChildren’s body mass index (BMI) z-score, sum of two-skinfolds (triceps and subscapular) and waist circumf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Furthermore, it is a limitation that information was not available for potentially key mediating variables, such as unhealthy snacking and meal times. Sleep restriction studies report increased snacking under short sleep conditions, particularly when participants would normally be asleep (Beebe et al, 2013; Nedeltcheva et al, 2009), and an investigation of young children found that an association of later sleep onset with higher adiposity was attenuated when adjusted for timing of the evening meal (Collings et al, 2021). Animal models and clinical trials of adult populations indicate that early and time‐restricted feeding has numerous physiological benefits, including lower adiposity (de Cabo & Mattson, 2019; Sutton et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is a limitation that information was not available for potentially key mediating variables, such as unhealthy snacking and meal times. Sleep restriction studies report increased snacking under short sleep conditions, particularly when participants would normally be asleep (Beebe et al, 2013; Nedeltcheva et al, 2009), and an investigation of young children found that an association of later sleep onset with higher adiposity was attenuated when adjusted for timing of the evening meal (Collings et al, 2021). Animal models and clinical trials of adult populations indicate that early and time‐restricted feeding has numerous physiological benefits, including lower adiposity (de Cabo & Mattson, 2019; Sutton et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It is a limitation that not all participating studies were nationally representative and the vast majority of participants were white. There is evidence for effect modification of sleep‐health associations by ethnicity, and hence caution is warranted before generalizing the results to non‐white youth 44,45 . All studies ascertained information for sleep by subjective reporting, and most studies asked about the time that participants usually went to bed and got out of bed.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence for effect modification of sleep-health associations by ethnicity, and hence caution is warranted before generalizing the results to non-white youth. 44,45 All studies ascertained information for sleep by subjective reporting, and most studies asked about the time that participants usually went to bed and got out of bed. The data for sleep duration may therefore be overestimated due to factors including screen-time engagement whilst in bed, sleep onset latency, overnight waking, and wakefulness on mornings prior to getting up (the latter three behaviours are, nevertheless, components of a normal sleep-wake cycle 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Develop a bedtime routine and keep to a consistent bedtime where possible, 59 , 118 as these practices promote better quality and duration of sleep in toddlers, 59 , 118 and possibly help to prevent obesity. 119 Pre-bedtime activities like storytelling or cuddling also help toddlers sleep better and longer. 120 Provide a dark and quiet environment with comfortable ambient temperature that is conducive for sleep, and avoid screen time at least 30 min before bedtime.…”
Section: Consensus Statementmentioning
confidence: 99%